Komunikasi Budaya Etnis Jawa dan Tionghoa di Tebing Tinggi Kota - Pratiwi, Pratiwi; Syahminan, Mhd (Riwayat: Educational Journal of History and Humanities, 2025)
This study examines the dynamics of cultural communication between the Javanese and Chinese ethnic groups in Tebing Tinggi City, North Sumatra, with a focus on the communication strategies used by the Chinese ethnic group as a minority group to adapt to the Javanese majority society. A qualitative approach using ethnography and ethnomethodology was employed to understand the interactions, communication styles, and barriers that arise in the daily lives of both ethnic groups. The research findings reveal that differences in value systems, linguistic politeness, and communication styles daily lives of both ethnic groups. The findings of the study indicate that differences in value systems, language etiquette, and communication styles between the two ethnic groups initially led to negative perceptions. However, through increased interaction, social participation, and adaptation efforts, both communities successfully built harmonious relationships within the framework of cultural diversity.